(untitled) - J G Manners (Cambridge, Massachusetts, 1993)
Whether a plant becomes diseased depends on the results of an interaction between the plant, the pathogen, and the environment. In this book the mechanisms underlying these interactions and the implications for effective disease control are discussed. In Part I the causes of plant disease are considered, and in Part II the physiological and biochemical processes involved in plant-pathogen interaction are discussed. Recent advances in the molecular biochemistry and genetics of pathogenesis, together with the classical genetics, form the subject of Part III while Part IV considers the epidemiology of plant disease, with particular attention to the application of modern mathematical techniques to forecasting. In final part, the implications of a study of these principles to practical plant disease control are assessed, with emphasis on cost-effectiveness and integrated disease control strategies
Keywords: plant diseases